The Youth Revolving Funds in alleviating poverty in Zimbabwe: A case of Youth Agenda Trust in Zengeza Suburbs. - Mawoyo, Tariro (Midlands State University, 2017)
The study investigates the effectiveness of the youth revolving fund in alleviating poverty in Zimbabwe. This will be brought about through using a case study of the Youth Agenda Trust’s involvement in Zengeza Suburbs from the period 2007-2014. The researcher made use of the questionnaires and interviews to collect data. A purposeful sample was used in choosing the beneficiaries of the youth revolving fund. Interviews were also conducted with the beneficiaries of the youth revolving fund from Zengeza. The organisation also contributed on these interviews. The study reveals that there is lack of transparency in issuing these funds, moreover the youths who would have benefited from the revolving fund are not being honest enough to return the funds as expected. However, some of these youths have benefited a lot from these youth revolving funds which has helped eradicate poverty in Zimbabwe. The study also reveals the indicators of effectiveness which are: percentage of people below the Total Consumption Poverty Line, Human Poverty Index and employment to population increase. The study also looks at the numbers of the youths who have been assisted by the youth revolving fund and the income generating projects that they have engaged in so as to eradicate poverty amongst the youths.